Study on Micropore Throat Fluid Seepage Characteristics and Oil Displacement Efficiency in Tight Reservoir. (7th October 2022) - Han, Jin; Wei, Yuhang; Chen, Xiaobing
Abstract : In order to overcome the problems including complicated pore throat structure, changeable seepage characteristics, and difficulty to find seepage law in the tight reservoir, this study simulated the water flooding development process of oilfield reservoir, and the water flooding seepage experiment of real sandstone microscopic model was carried out in a laboratory. Thin slice identification, constant velocity mercury injection, physical property analysis, scanning electron microscope, and other test data were combined to study the reservoir microscopic water flooding characteristics. The relationships between physical properties, water displacement efficiency, displacement pressure, pore structure, wettability, and water injection ratio are discussed. The study showed that the tight reservoir fluids were uniform displacement and reticular displacement seepage that occurred more than finger-reticular displacement. Meanwhile, displacement types affected oil displacement efficiency. Specifically, the uniform displacement type displayed the highest oil displacement efficiency, whose average value was 62.15%. The lowest oil displacement efficiency was finger displacement type, which is 26.89%. Additionally, 79% of the residual oil was cluster and film, and the corner and isolated distribution are less; the change of permeability has a greater effect on oil displacement efficiency than porosity. With the increase of water injection ratio, the oil displacement efficiency was improved. The oil displacement efficiency increases greatly and tended to be smooth and stable, when the water injection increased by 3 PV. There is an exponential relationship between throat radius and oil displacement efficiency.